Studi Perbandingan Level Kinerja Struktur Bangunan-Bangunan Ruko di Wilayah Surabaya - Hendra Junianto; Bantot Sutriono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Earthquakes are one of the lateral loads that can cause significant damage to multi-story buildings; therefore, structural systems with good seismic resistance and performance are required. This study aims to evaluate and compare the dynamic behavior of several multi-story shop-house (ruko) models under earthquake loading by examining key parameters such as structural displacement, natural period, base shear force, and the influence of the P-Delta effect. The analysis results show that each ruko model exhibits different dynamic responses to earthquake loads depending on its stiffness and flexibility characteristics. Ruko A performs best in controlling displacement and the P-Delta effect, Ruko B is the stiffest with relatively stable responses, Ruko C is the most efficient in resisting lateral forces, while Ruko D is the most flexible but produces the largest structural response. Therefore, optimal structural performance is not determined by a single parameter, but rather by a balance between stiffness, displacement, and internal forces.